Clinical and radiographic outcomes of implant‐supported fixed dental prostheses with cantilever extension. A retrospective cohort study with a follow‐up of at least 10 years. Issue 12 (17th October 2020) - Schmid, Eric; Morandini, Michele; Roccuzzo, Andrea; Ramseier, Christoph A.; Sculean, Anton; Salvi, Giovanni E.
Abstract: Aim: To report the clinical and radiographic outcomes of implant‐supported fixed dental prostheses with cantilever extensions (FDPCs) after a function time ≥10 years. Material and methods: Patients with FDPCs in posterior areas were clinically and radiographically re‐evaluated. Mesial and distal radiographic marginal bone levels (mBLs) from baseline (i.e. delivery of FDPC) to the follow‐up examination were calculated and compared between implant surfaces adjacent to and distant from the cantilever extension. Implant survival rate, pocket probing depth (PPD), presence/absence of bleeding on probing (BoP) and presence/absence of mechanical/technical and biological complications were recorded. Results: Twenty‐six patients with 30 FDPCs supported by 60 implants were re‐evaluated after a mean loading time of 13.3 ± 2.7 years (range: 10–18.6 years). One diameter‐reduced implant carrying a cantilever extension fractured, yielding a patient‐based survival rate of 96.2% (95% CI: 0.95/1.0). The mean marginal bone level change was not statistically significantly different from baseline to follow‐up (1.2 mm ± 0.9 to 1.6 mm ± 1.7; 95% CI: −0.1/0.9; p > .05). The mean PPD changed statistically significantly from 3.4 mm ± 0.7 to 3.7 mm ± 0.7 (95% CI: 0.04/0.6; p = .02). Loss of retention occurred ≥ 1x in 9 patients (34.6%, 95% CI: 0.44/0.83). At follow‐up, peri‐implant health was diagnosed in 12 (46.2%), peri‐implant mucositis in 7 (26.9%) and peri‐implantitis in 7 (26.9%) patients, respectively. Conclusion: Despite a high rate of loss of retention, the use of implant‐supported FDPCs in posterior areas represents a reliable long‐term treatment option with a high implant survival rate and minimal peri‐implant bone level changes irrespective of the location of the cantilever extension.